2006
DOI: 10.1510/icvts.2006.133710
|View full text |Cite
|
Sign up to set email alerts
|

The bidirectional cavopulmonary (Glenn) shunt without cardiopulmonary bypass: is it a safe option?

Abstract: Our results show that in selected patients, bidirectional Glenn operation without cardiopulmonary bypass is a safe procedure. It avoids cardiopulmonary bypass related problems and is economical, with excellent results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 12 publications
0
44
1
4
Order By: Relevance
“…There is one report 7 of decompression by aspirating the SVC with a syringe. It seems to be reasonable to use a shunt though our report and the reports by Jahangiri 4 and Hussain 14 show that it is by no means mandatory.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…There is one report 7 of decompression by aspirating the SVC with a syringe. It seems to be reasonable to use a shunt though our report and the reports by Jahangiri 4 and Hussain 14 show that it is by no means mandatory.…”
Section: Discussionmentioning
confidence: 51%
“…Leaving the azygous vein open during the construction of the anastomosis has been put forward as an internal shunt 14 . Others believe that since the azygous vein is valved, its role in decompressing the SVC is doubtful.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Although such reports have documented no significant differences in neurological sequelae after clamping the SVC without the use of any shunt, we believe that clamping the SVC without a temporary shunt may lead to decreased cerebral blood flow and put the brain at risk. [12,13] In a study, Liu et al [13] reported that BCPA without CPB was reasonably safe, if SVC pressure after clamping remained at less than 30 mmHg and clamping time was less than 30 minutes. In consistent with these findings, the mean SVC clamping time and SVC pressure after clamping remained at less than 30 minutes and 30 mmHg, respectively, without any neurological complications in our study cohort.…”
Section: Discussionmentioning
confidence: 99%
“…It can be performed with or without cardio-pulmonary bypass as far as the pulmonary perfusion is maintained. [1,2] During the procedure, the superior vena cava (SVC) is clamped and the proximal pressures can rise as high as 40 to 55 mmHg. This impairs blood flow to the brain (Cerebral perfusion pressure = Mean arterial pressure -Central venous pressure).…”
Section: Introductionmentioning
confidence: 99%